2008
DOI: 10.1523/jneurosci.4878-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Blockade of RAGE-VdPrevents Amyloid-β Oligomer Neurotoxicity

Abstract: In the genesis of Alzheimer's disease (AD), converging lines of evidence suggest that amyloid-␤ peptide (A␤) triggers a pathogenic cascade leading to neuronal loss. It was long assumed that A␤ had to be assembled into extracellular amyloid fibrils or aggregates to exert its cytotoxic effects. Over the past decade, characterization of soluble oligomeric A␤ species in the brains of AD patients and in transgenic models has raised the possibility that different conformations of A␤ may contribute to AD pathology vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 70 publications
(104 reference statements)
3
85
0
Order By: Relevance
“…The major features of RAGE activation in contributing to AD result from its interaction with A␤. RAGE interaction with A␤ results in perturbation of neuronal function, amplification of glial inflammatory response, elevation of oxidative stress and amyloidosis, and increased A␤ influx at the BBB (75)(76)(77)(78). Our results suggest that A␤-RAGE interaction at the BBB links the intracerebral A␤ deposition to systemic immune T cells by up-regulating CCR5 on brain endothelial cells.…”
Section: Discussionmentioning
confidence: 65%
“…The major features of RAGE activation in contributing to AD result from its interaction with A␤. RAGE interaction with A␤ results in perturbation of neuronal function, amplification of glial inflammatory response, elevation of oxidative stress and amyloidosis, and increased A␤ influx at the BBB (75)(76)(77)(78). Our results suggest that A␤-RAGE interaction at the BBB links the intracerebral A␤ deposition to systemic immune T cells by up-regulating CCR5 on brain endothelial cells.…”
Section: Discussionmentioning
confidence: 65%
“…Notably, the amounts of Aβ deposits and plaques increase by overexpression of fulllength RAGE, not by sRAGE (Cho et al, 2009). RAGE binds to diverse forms of Aβ: Aβ oligomer and aggregate and nonfibrillar and fibrillar forms of Aβ (Sturchler et al, 2008;Verdier et al, 2004). Kinetic studies suggest that purified RAGE binds specifically to Aβ (K d = 57 ± 14 nM), similar to K d values in endothelial and cortical neurons (40 ± 10 nM and 55 ± 15 nM, respectively) .…”
Section: Rage and Aβmentioning
confidence: 72%
“…In addition, different binding sites can exist for aggregated ligands. RAGE is implicated in Aβ oligomer-and Aβ aggregate-induced apoptosis in SH-SY5Y cells (not Aβ fibrils), and distinct regions of RAGE mediate the binding of various conformations of Aβ; the V d domain is important for Aβ oligomer binding to RAGE, and the C 1d domain controls the ligation of Aβ aggregates (Sturchler et al, 2008).…”
Section: Rage and Aβmentioning
confidence: 99%
“…Many of these molecules are critical elements responsible for shaping and maintaining anatomical structures on neurons and mediating signaling pathways that control neuronal communication. In recent years, numerous studies have identified several putative receptors for Aβ oligomers, including α7-nAChR (7), RAGE (8), PrP c (9), mGluR5 (10,11), insulin receptor (12), EphB2 receptor (13,14), human LilrB2 (15), the p75 neurotrophic receptor (16) and reelin (17). Interaction of Aβ oligomers with these receptors might constitute crucial events leading to morphological and functional changes of dendritic spines associated with cognitive impairment in AD (4,18).…”
Section: Evidence For the Presence And Role Of Xbp1 In Dendritic Spinesmentioning
confidence: 99%